Emergence of verbal responses using instructive feedback: A replication and extension. (29th October 2021) - Tullis, Christopher A.; Gibbs, Ashley R.; Priester, Jocelyn; Tillem, Alix
Abstract: Few studies have investigated the potential of instructive feedback (IF) procedures to result in the emergence of novel‐related verbal responses. Furthermore, few studies have directly assessed the role self‐echoic behavior may have in IF procedures. The current replication and extension evaluated the effects of IF procedures during unmastered primary target trials on the emergence of novel verbal responses. All learners acquired primary, secondary, and related, but unpresented, verbal responses, and maintained responding for 2 months. These results extend the IF literature by providing evidence that IF may facilitate the emergence of novel verbal responses during skill acquisition.